THE CORRELATION BETWEEN THE ERYTHROCYTE INDEX AND THE EXTENT OF TUBERCULOSIS LESIONS IN THORAX RADIOGRAPHY - Azmi, Mukhammad; Yueniwati, Yuyun; Rachma Erawati, Dini (Journal of Community Health and Preventive Medicine, 2024)
Tuberculosis is a contagious disease and is one of the ten leading causes of death in the world. Abnormalities in the hematology system, such as anemia, become one of the complications due to tuberculosis infection. The erythrocyte index becomes a benchmark for determining anemia based on its size and appearance. In tuberculosis patients, tuberculosis lesions can be seen in a thorax radiography examination. Therefore, the objective of this study was to determine the correlation between the erythrocyte index and the extent of tuberculosis lesions in thorax radiography. This study was an observational study using the cross-sectional method by taking 61 samples of patients' medical records in Saiful Anwar Hospital, which was conducted from January 2022 to December 2023. In this study, data obtained that MCV, MCH, and MCHC, which included in erythrocyte index value, did not have a correlation with the extent of tuberculosis lesion (p=0.656, p=0.484 and p=0.953, respectively, using Kruskal Wallis method). This could occur because tuberculosis patients only experienced anemia with a reduced number of erythrocytes without affecting their size and appearance. The conclusion of this study is that the erythrocyte index does not have a correlation with the extent of tuberculosis lesions.